2012
DOI: 10.1177/1479972312459973
|View full text |Cite
|
Sign up to set email alerts
|

Systemic comorbidities in bronchiectasis

Abstract: Bronchiectasis is a chronic inflammatory lung disease, which has similarities to chronic obstructive pulmonary disease (COPD). Comorbidities of COPD include increased risk of cardiovascular (CV) disease, loss of bone mineral density (BMD) and loss of skeletal muscle mass and function, all linked to systemic inflammation. The potential for such comorbidities has not been explored in bronchiectasis. We hypothesised that patients with bronchiectasis would have similar increased comorbidities. A total of 20 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 28 publications
4
48
0
1
Order By: Relevance
“…We also found no change in PFT and dyspnoea after H‐IMT in patients with bronchiectasis, similar to the previous studies using IMT . The smoking history was minimal which is similar to the previous findings in patients with bronchiectasis . The findings may reveal that H‐IMT does not affect expiratory airflow and breathlessness in mild lung function impairment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found no change in PFT and dyspnoea after H‐IMT in patients with bronchiectasis, similar to the previous studies using IMT . The smoking history was minimal which is similar to the previous findings in patients with bronchiectasis . The findings may reveal that H‐IMT does not affect expiratory airflow and breathlessness in mild lung function impairment.…”
Section: Discussionsupporting
confidence: 90%
“…5,8 The smoking history was minimal which is similar to the previous findings in patients with bronchiectasis. 25 The findings may reveal that H-IMT does not affect expiratory airflow and breathlessness in mild lung function impairment. Chronic fatigue is frequent in bronchiectasis and may affect exercise capacity and QOL.…”
Section: Discussionmentioning
confidence: 90%
“…Troosters et al [13] reported that 75% of adult patients with stable CF (mean FEV 1 65% of the predicted value) have a 6-min walking distance below the limits of normal, while up to 90% of these patients showed a decreased peak aerobic capacity. A decreased 6-min walking distance has also been reported in non-CF bronchiectasis [15]. …”
Section: Exercise Intolerancementioning
confidence: 99%
“…Moderate-intensity activities are typically considered necessary to maintain physical fitness [48]. In non-CF bronchiectasis, objective outcomes of physical activity are not available, but self-reported physical activity is also decreased [15]. …”
Section: Reasons For a Reduced Exercise Capacitymentioning
confidence: 99%
“…This may be associated with inflammation and progressive tissue destruction with abnormal lung function [2,3,4,5]. Clinically, it is characterised by chronic and commonly purulent sputum expectoration, fatigue, reduced exercise capacity and progressive dyspnoea that can become disabling [2,3,4,5,6,7,8]. People with non-CF bronchiectasis frequently experience recurrent acute exacerbations due to a vicious cycle of persistent infection and inflammation [9,10].…”
Section: Introductionmentioning
confidence: 99%